Robotic Management of Urolithiasis in the Pediatric Population - Ballesteros, Natalia; Snow, Zachary A.; Moscardi, Paulo R. M.; Ransford, George A.; Gomez, Pablo; Castellan, Miguel (Frontiers in Pediatrics, 2019)
A variety of surgical techniques exist for the management of urolithiasis. Minimally invasive techniques have replaced open surgery in the last few decades. For complex stone management, robotic-assisted laparoscopic surgery (RALS) has emerged as a safe and feasible alternative in adults. The literature for RALS for urolithiasis (RALS-UL) in the pediatric population is scarce. Herein, we present a review of the literature in both adult and pediatric patients as well as our experience using RALS-UL at our institutions. Special attention is given to the synchronous management of urolithiasis when surgery is performed for other conditions such as ureteropelvic junction obstruction (UPJO).